2020
DOI: 10.3389/fpsyg.2020.02246
|View full text |Cite
|
Sign up to set email alerts
|

The Development of an Instrument for Longitudinal Learning Diagnosis of Rational Number Operations Based on Parallel Tests

Abstract: The precondition of the measurement of longitudinal learning is a high-quality instrument for longitudinal learning diagnosis. This study developed an instrument for longitudinal learning diagnosis of rational number operations. In order to provide a reference for practitioners to develop the instrument for longitudinal learning diagnosis, the development process was presented step by step. The development process contains three main phases, the Q-matrix construction and item development, the preliminary/pilot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Table 1 summarizes the model‐data fit indices of the four models. According to the DIC, the following was found: (a) the hierarchical model fit the data better than its corresponding model that did not consider attribute hierarchy, indicating models that consider attribute hierarchy are more appropriate for analyzing data containing hierarchical attributes; and (b) the DINA‐based models fit the data better than the LLM‐based models, indicating these six attributes may follow the conjunctive condensation rule (see Tang & Zhan, 2020b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 summarizes the model‐data fit indices of the four models. According to the DIC, the following was found: (a) the hierarchical model fit the data better than its corresponding model that did not consider attribute hierarchy, indicating models that consider attribute hierarchy are more appropriate for analyzing data containing hierarchical attributes; and (b) the DINA‐based models fit the data better than the LLM‐based models, indicating these six attributes may follow the conjunctive condensation rule (see Tang & Zhan, 2020b).…”
Section: Resultsmentioning
confidence: 99%
“…To illustrate the application of the proposed models, we used data from a quasi‐experiment that evaluated the effectiveness of different feedback modes on promoting learning in the content of rational number operations (Tang & Zhan, 2020a). The development of the instrument for this quasi‐experiment has been described in detail by Tang and Zhan (2020b), and the data were recently used by Zhan (2020c).…”
Section: An Empirical Studymentioning
confidence: 99%
“…Since the development process is not the focus of this study, we only give a brief introduction to it, and more details about it can be found in Tang and Zhan (2020). The development process contains three main phases: (a) the Q-matrix (Tatsuoka, 1983) construction and item development, (b) the pilot test for item quality monitoring (the preliminary screening of the items is conducted mainly according to item difficulty and discrimination based on classical test theory), and (c) the formal test for test quality control (including the Q-matrix validation [de la Torre, 2008], reliability and validity testing [W. Wang et al, 2015], differential item functioning checking [Hou et al, 2014], and parallel tests checking).…”
Section: Instrumentmentioning
confidence: 99%
“…Three parallel tests had the same Q‐matrix (see Figure 4), which contained 18 dichotomous items (i.e., 54 items in total) and six fine‐grained attributes, namely, (A1), rational number; (A2), related concepts of the rational number; (A3), number axis; (A4), addition and subtraction of rational numbers; (A5), multiplication and division of rational numbers; and (A6), mixed operation of rational numbers. More details about this instrument used in the quasi‐experiment can be found in Tang and Zhan (2020). The results of this quasi‐experiment mainly indicated that both learning diagnostic feedback and traditional correct‐incorrect response feedback could promote student learning, but the former was significantly more effective than the latter.…”
Section: An Empirical Examplementioning
confidence: 99%